COMPARISON OF CYTOLOGICAL AND HISTOPATHOLOGICAL FINDINGS IN BREAST LESIONS – A TERTIARY CARE CENTER - Bharatkumar, Patel Hani; Samanta, Matariswa; Nikhra, Pawan; Behl, Vishakha; Ashvinbhai, Patel Ujaskumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to compare the findings of cytological and histopathological features of breast lesions. Methods: This study conducted on 109 patients with breast lump with fine needle aspiration cytology (FNAC) followed by histopathology at Department of Pathology, Pacific Institute of Medical Sciences, Umarda, Udaipur, Rajasthan. The study duration is 18-month study period (April 2021 to September 2022). Results: The mean age of the study subjects was 44.20 years with majority of the patients belonged to the age group 41–50 years (36.70%). Out of 109 cases, 84 cases (77.07%) were benign and 23 cases (21.10%) were malignant pathology in FNAC. Rest two cases had intermediate pathology. Majority of histopathological diagnosis of breast lumps in the present study were benign pathology (75.23%) and rest all malignant (24.77%). Conclusion: Our study shows that FNAC can reliably distinguish between benign and malignant conditions and it is a sensitive and specific modality that assist in diagnosis and management of breast lesions. Although FNAC has been found to be a most valuable economic, simple, and safe diagnostic procedure, due to certain pitfall of FNAC like in case of pauci-cellularity blood mixed aspirates and blind technique procedure. Histopathological correlation is always mandatory for early diagnosis and better prognosis.